Optimization of particle size and ramie fiber ratio on hybrid bio panel production from oil palm trunk as thermal insulation materials - Mawardi, Indra; Nurdin, .; Fakhriza, .; Rizal, Samsul; Sri Aprilia, .; Faisal, Muhammad; Putra Jaya, Ramadhansyah (Lublin University of Technology, 2023)
The abundant availability of waste oil palm trunks is one of the potential fiber for new thermal insulation materials. While focusing on manufacturing thermal insulation materials, the main points to be considered are particle size, reinforcement fiber ratio, and press durations, besides binders type and temperature. This study aims to optimize the manufacturing process of hybrid bio panels based on oil palm trunks as thermal insulation material. The response surface methodology (RSM), with a Box-Behnken Design (BBD), was used to model and optimize the manufacturing process variables. A total of 17 hybrid bio panels were in the operation and the independent variables used were particle size, ramie ratio, and press duration. The dependent variables were water absorption, thickness swelling, MOR, and thermal conductivity. The hybrid bio panel obtained under the optimum condition was characterized by thermogravimetric analysis to observe thermal stability. Based on analysis of variance and the contour plot, it was discovered that the interaction between particle size and ramie fiber ratio was the significant variable to optimize hybrid bio panel manufacture. The thermal resistance and modulus of rupture of hybrid bio panels also improved with higher particle size and ramie fiber ratio. The optimum manufacturing process was obtained at OPT particle size of 0.248 mm, ramie fiber ratio of 19.775, and press duration of 25 min. This condition produces a thermal conductivity of 0.079 W/mK, modulus of rupture of 17.702 MPa, water absorption of 54.428 %, and thickness swelling of 21.974 %. In addition, the hybrid bio panel resulted in thermal stability of 341°C.